The Financial Dearth of University Libraries in Ghana: The University of Science and Technology Library in Perspective - Bani, Emmanuel Kofi (Ghana Library Journal, 2000)
The library is an essential component of the University system and needs to be adequately funded in order to perform satisfactorily. University Libraries in Ghana, in general, and UST, Kumasi, in particular, have for a long time grappled with inadequate funding. A 1988 survey revealed that the university libraries in Ghana on the average were receiving 2.02% of the universities' vote in the 1980' s, the least allocation to any unit in the universities. The trend persists to the present day. The financial problem of the library is traced to the general insufficient government grant to the universities and the universities in turn allocating a negligible percentage of it to the library. The quarterly release of the subvention by the government contributes immensely to the problem.The formula for allocating the grants to the faculties, institutes, centres and other units particularly at UST does not seem to favour the library much. The Finance Officers in turn, do not appear to be disposed to the course of the Library. The paper makes recommendations for concrete financial policies to be drawn for the libraries; for an increase in the vote allocation to the libraries; and for the strengthening of the Library Committee.